WPAP PADA TAS DENGAN TEKNIK MAKRAME DAN TAPESTRI - LAILA AFRILIANI, Drs. Erwin, M.Sn., Dra. Ernis, M.Pd. (Serupa The Journal of Art Education, 2018)
This final paper discusses WPAP Wedha’s Pop Art Potrait is art illustration of face potrait crossed by geometry with special color. Then visualized in woven works the purpose of the creation of this final work embodies the bag of woven and living creatures with makrame and tapestri techniques into the form of woven bags.Methods of creating artwork, using five stages preparatory stage, elaboration stage, realization stage of concept and completion stage, and the last one to hold the final work exhibition. In the creation of the work, the auther uses makrame and tapestri techniques. Because previously most people use makrame techniques alone rarely combine the two techniques.Seven works created on the creative economy because the young Generation of Indonesia is know to have the creativity and the ability to create new product especially those culture such as batik, songket, embroidery, craft wood craft and wicker craft.